Secured Data Transmission Using Wavelet Based Steganography and Cryptography by Using AES Algorithm - Reddy, M. Indra Sena; Kumar, A.P. Siva (Procedia computer science, 2016)
Steganography and cryptography methods are used together with wavelets to increase the security of data while transmitting through networks. In discrete wavelet transform, “analysis filter bank “can be used for analyzing image signal by passing through it. This filter bank consists of a low pass and a high pass filter at each decomposition stage. The digital watermarking plays an important role in embedding information into a digital image signal, for verification and identity of its owners. In this paper the embedded information is applied as text. Before embedding the text in image, text is encrypted using Advanced Encryption Standard (AES) algorithm. The text can be a sentence or a key with alphabetic words having the length of 8 characters. Using Least Significant Bit (LSB) method, the encrypted text is embedded into the “LL sub-band wavelet decomposed image”. The inverse wavelet transform is applied and the resultant image is transmitted to the receiver. Now at the receiver”s end, the image transformed using wavelet and encrypted text is extracted by using LSB method. The paper also shows how the AES algorithm is used in decryption of result.